2007
DOI: 10.1007/s00423-006-0143-4
|View full text |Cite
|
Sign up to set email alerts
|

Radical lymph node resection of the retroperitoneal area for left-sided colon cancer

Abstract: Radical lymph node resection of the retroperitoneal area is associated with the same rate of hospital morbidity, late urogenital morbidity, and total survival as is conventional surgery. It seems that there is a trend for improvement of survival particularly in stage III patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…Based on the literature, there may be selection and publication bias. The 30-day mortality rate found in this study is similar to findings reported previously by others 5,14,19,20 . This study also reported 90-day mortality, as the elderly and patients with co-morbidities have an increased risk of dying between 30 and 90 days after surgery 21 -23 .…”
Section: Discussionsupporting
confidence: 94%
“…Based on the literature, there may be selection and publication bias. The 30-day mortality rate found in this study is similar to findings reported previously by others 5,14,19,20 . This study also reported 90-day mortality, as the elderly and patients with co-morbidities have an increased risk of dying between 30 and 90 days after surgery 21 -23 .…”
Section: Discussionsupporting
confidence: 94%
“…Seven were documented as prospective cohort studies. Five series had controls, of which only one was randomized [3,4,[23][24][25]. The total analysable included population was 5246 CME/ EL cases.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The mean age of the patients included was 62.2 years (five studies did not include patient age or gender) and 56.5% were men [4,10,[23][24][25]. Approximately 50% of neoplasms were right-sided lesions ( Table 2).…”
Section: Baseline Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although radical resection resulted in a significantly higher LNC, no difference in the number of positive nodes or survival was found. Similarly, a prospective single-center trial by Tentes et al [36] compared periaortic LN resection for left-sided CC with conventional surgery in 124 patients. Again, despite a significantly higher LNC after radical resection, no significant difference in the number of involved nodes or survival was noted although improved survival in stage III patients was found after radical resection ( p = 0.04).…”
Section: Clinical Studies Comparing the Extent Of Lymphadenectomymentioning
confidence: 99%